2004
DOI: 10.1063/1.1806564
|View full text |Cite
|
Sign up to set email alerts
|

Submonolayer InGaAs∕GaAs quantum-dot lasers with high modal gain and zero-linewidth enhancement factor

Abstract: The gain spectra of a submonolayer (SML) InGaAs∕GaAs quantum dot (QD) laser working at 30°C were measured using the Hakki–Paoli method. It is found that the maximum modal gain of QD ground states is as high as 44cm−1 and no gain saturation occurs below the threshold at the lasing wavelength of 964.1nm. When the injection current is about 0.98 times the threshold, the gain spectrum becomes symmetric with respect to the lasing wavelength, and zero-linewidth enhancement factor is observed. These properties are at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…1 The radiative lifetime of the excitons in QDs at room temperature is one of the most important device parameters, being inversely proportional to the modal gain of QD lasers. [2][3][4][5] The radiative lifetime of strongly confined excitons in QDs, where the energy separation between the ground state and the first excited exciton state is larger than the thermal energy k B T ͑k B is the Boltzmann constant and T is the temperature͒, should be almost independent of T. However, in real QDs, the radiative lifetime of the ground state excitons is expected to increase with increasing temperature due to the thermal population of optically inactive or poorly active exciton states. [6][7][8] This phenomenon was first observed in InGaAs/GaAs QDs by Wang et al 9 in 1994, in InAs/GaAs QDs by Yu et al 10 in 1996, and by other groups later.…”
mentioning
confidence: 99%
“…1 The radiative lifetime of the excitons in QDs at room temperature is one of the most important device parameters, being inversely proportional to the modal gain of QD lasers. [2][3][4][5] The radiative lifetime of strongly confined excitons in QDs, where the energy separation between the ground state and the first excited exciton state is larger than the thermal energy k B T ͑k B is the Boltzmann constant and T is the temperature͒, should be almost independent of T. However, in real QDs, the radiative lifetime of the ground state excitons is expected to increase with increasing temperature due to the thermal population of optically inactive or poorly active exciton states. [6][7][8] This phenomenon was first observed in InGaAs/GaAs QDs by Wang et al 9 in 1994, in InAs/GaAs QDs by Yu et al 10 in 1996, and by other groups later.…”
mentioning
confidence: 99%
“…Indeed, a reduced (or even negative) α-factor and a reduced tendency to beam filamentation was observed in many QD samples, at least under some operating conditions. [26][27][28][29][30][31] The real susceptibility of QD are more complicated than the one of a two-level atom due to contributions from the wetting layer, higher QD states and inhomogeneous broadening (e.g. 32 ), though the possibility of a negative α−factor under gain conditions can survive.…”
Section: Discussionmentioning
confidence: 99%
“…10 The PL signal from the SML QD ground state can be observed even at room temperature if we increase the growth temperature of SML QDs to 500°C. 11 Lasers using high-temperature grown ͑HTG͒ SML QDs show very high modal gain and zero linewidth enhancement factor. 11 In this letter, we report the exciton radiative lifetime of HTG SML QDs from 10 to 260 K, via time-resolved photoluminescence ͑TRPL͒.…”
mentioning
confidence: 99%
“…11 Lasers using high-temperature grown ͑HTG͒ SML QDs show very high modal gain and zero linewidth enhancement factor. 11 In this letter, we report the exciton radiative lifetime of HTG SML QDs from 10 to 260 K, via time-resolved photoluminescence ͑TRPL͒. We found that the exciton radiative lifetime in SML QDs is around 90 ps and is almost independent of temperature below 50 K.…”
mentioning
confidence: 99%